2020
DOI: 10.1038/s41597-020-00710-z
|View full text |Cite
|
Sign up to set email alerts
|

SynergyAge, a curated database for synergistic and antagonistic interactions of longevity-associated genes

Abstract: Interventional studies on genetic modulators of longevity have significantly changed gerontology. While available lifespan data are continually accumulating, further understanding of the aging process is still limited by the poor understanding of epistasis and of the non-linear interactions between multiple longevity-associated genes. Unfortunately, based on observations so far, there is no simple method to predict the cumulative impact of genes on lifespan. As a step towards applying predictive methods, but a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A gene may impact longevity not only by itself, but also by cooperation with other genes. Based on the cumulative knowledge of interactions between longevity-associated genes (LAGs), it has been previously shown that genes that have a role in determining average or maximum lifespan (as LAGs for example) may have a variety of combined effects—synergistic, additive, dependent, or antagonistic [ 40 ]. Thus, the total lifespan changes as a result of genetic interventions targeting two genes are usually not the simple sum of their impacts.…”
Section: Resultsmentioning
confidence: 99%
“…A gene may impact longevity not only by itself, but also by cooperation with other genes. Based on the cumulative knowledge of interactions between longevity-associated genes (LAGs), it has been previously shown that genes that have a role in determining average or maximum lifespan (as LAGs for example) may have a variety of combined effects—synergistic, additive, dependent, or antagonistic [ 40 ]. Thus, the total lifespan changes as a result of genetic interventions targeting two genes are usually not the simple sum of their impacts.…”
Section: Resultsmentioning
confidence: 99%
“…At day 15, the odr-3;ife-2 animals still showed approximately 42 contractions per minute (compared to 15 contractions per minute in the WT), a 187% increase (p <E-04). On day 15, the odr-3(n1605) and ife-2(ok306) mutations showed a synergistic effect on the pharyngeal pumping, the increase observed in the double mutant being higher than the sum of the individual effects (187% increase compared to 66% + 55% increase for single mutants), corresponding to a fully synergic effect [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the existence of complex and intricate interactions between hundreds of longevity-associated genes [ 62 64 ], the lifespan modulation obtained with these methods was limited by how much a single gene can influence longevity. While combined genetic interventions that modulate longevity via parallel pathways or drugs targeting multiple evolutionary conserved aging pathways have been shown in many instances to extend lifespan [ 65 ], the number of gene combinations tested so far has not been very high [ 18 ]. Here, we assessed the effects on both lifespan and healthspan, given by the simultaneous inactivation of three genes: odr-3 , ife-2 and cku-70 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations